2010
DOI: 10.1038/aps.2010.9
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ginsenoside Rb3 on oxygen and glucose deprivation-induced ischemic injury in PC12 cells

Abstract: Aim: To investigate the protective effects of ginsenoside Rb 3 , a triterpenoid saponin isolated from the leaves of Panax notoginseng, on ischemic and reperfusion injury model of PC12 cells and elucidate the related mechanisms. Methods: PC12 cells exposed to oxygen and glucose deprivation (OGD) and restoration (OGD-Rep) were used as an in vitro model of ischemia and reperfusion. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and lactate dehydrogenase (LDH) leakage were used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…The activity of LDH in culture medium could also be used as a marker of cell injury. LDH is a stable cytoplasmic enzyme that is present in most cells, and is rapidly released into the culture medium following plasma membrane damage (Zhu et al, 2010). As shown in Fig.…”
Section: Effects Of Ator On the Nad þ Content In Myocardial Tissuementioning
confidence: 99%
“…The activity of LDH in culture medium could also be used as a marker of cell injury. LDH is a stable cytoplasmic enzyme that is present in most cells, and is rapidly released into the culture medium following plasma membrane damage (Zhu et al, 2010). As shown in Fig.…”
Section: Effects Of Ator On the Nad þ Content In Myocardial Tissuementioning
confidence: 99%
“…It can acquire neuron-like properties when exposed to nerve growth factor (NGF) [12] . Therefore, it is widely used as an in vitro model of cerebral ischemia/reperfusion [13,14] . Intracellular free calcium concentration ([Ca 2+ ] i ) and mitochondrial membrane potential (MMP) are important indicators to reflect cell injury.…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside Rb1 could reduce the cortical infarct volume by approximately 50% and decrease the number of TUNEL-positive cells in the hippocampal CA1 region after ischemia [16]. Zhu et al [17] reported that ginsenoside Rb3 could markedly protect OGD-induced ischemic injury on PC12 cells. In our previous studies, we found that ginsenoside Rb3 exhibited the better neuroprotective effect than ginsenoside Rb1 in rat hippocampal slices using an in vitro ischemic model [6], but the underlying mechanism of action was still unclear.…”
Section: Discussionmentioning
confidence: 99%